Decreased circulating visfatin is associated with improved disease activity in early rheumatoid arthritis: data from the PERAC cohort - Sglunda, Ondřej; Mann, Heřman; Hulejová, Hana; Kuklová, Markéta; Pecha, Ondřej; Pleštilová, Lenka; Filková, Mária; Pavelka, Karel; Vencovský, Jiří; Senolt, Ladislav (PloS one, 2014)
OBJECTIVE: To evaluate circulating visfatin and its relationship with disease activity and serum lipids in patients with early, treatment-naïve rheumatoid arthritis (RA). METHODS: Serum visfatin was measured in 40 patients with early RA before and after three months of treatment and in 30 age- and sex-matched healthy individuals. Disease activity was assessed using the Disease Activity Score for 28 joints (DAS28) at baseline and at three and 12 months. Multivariate linear regression analysis was performed to evaluate whether improved disease activity is related to serum visfatin or a change in visfatin level. RESULTS: Serum visfatin was significantly elevated in early RA patients compared to healthy controls (1.92±1.17 vs. 1.36±0.93 ng/ml; p = 0.034) and significantly decreased after three months of treatment (to 0.99±0.67 ng/ml; p<0.001). Circulating visfatin and a change in visfatin level correlated with disease activity and improved disease activity over time, respectively. A decrease in visfatin after three months predicted a DAS28 improvement after 12 months. In addition, decreased serum visfatin was not associated with an improved atherogenic index but was associated with an increase in total cholesterol level. CONCLUSION: A short-term decrease in circulating visfatin may represent an independent predictor of long-term disease activity improvement in patients with early RA.
Keywords: lineární modely; Cholesterol; Humans; cholesterol; lidé středního věku; C-reaktivní protein; kohortové studie; Arthritis, Rheumatoid; Multivariate Analysis; antirevmatika; Nicotinamide Phosphoribosyltransferase; Female; Aged; dospělí; lipidy; Time Factors; výsledek terapie; senioři; lidé; nikotinamidfosforibosyltransferasa; časové faktory; Cohort Studies; revmatoidní artritida; Adult; ženské pohlaví; multivariační analýza; stupeň závažnosti nemoci; Male; Middle Aged; Linear Models; Treatment Outcome; Lipids; Severity of Illness Index; mužské pohlaví; C-Reactive Protein; Antirheumatic Agents